The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s13399-022-02944-w
|View full text |Cite
|
Sign up to set email alerts
|

Dual biogas/biochar production from anaerobic co-digestion of petrochemical and domestic wastewater: a techno-economic and sustainable approach

Abstract: This study investigates the utilization of petrochemical and domestic wastewater (PCW and DW) for dual biogas and biochar production, focusing on the economic and sustainable development criteria. Biogas yield by anaerobic co-digestion of a 0:1 (PCW:DW) feed was 306.4±11.8 mL per g chemical oxygen demand (COD) removed, which dropped by 12.7% with changing PCW:DW to 1:0. The results indicated that increasing the DW fraction in the feed encouraged the conversion of COD into more biogas and sludge amounts. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It is associated with the hydrogen vibration of the hydroxyl groups of alcohols, phenols, organic acids, or by amides (present in proteins and peptides) [62,63]. The intensity of this peak was maintained in the uncarbonized and carbonized biomass, which could indicate that the hydroxyl groups did not decompose after the thermochemical process at high temperatures [64] pikes 2950-2800 cm −1 correspond to aliphatic stretching (CH groups). This stretch was found in biochar and feedstock.…”
Section: Codmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with the hydrogen vibration of the hydroxyl groups of alcohols, phenols, organic acids, or by amides (present in proteins and peptides) [62,63]. The intensity of this peak was maintained in the uncarbonized and carbonized biomass, which could indicate that the hydroxyl groups did not decompose after the thermochemical process at high temperatures [64] pikes 2950-2800 cm −1 correspond to aliphatic stretching (CH groups). This stretch was found in biochar and feedstock.…”
Section: Codmentioning
confidence: 99%
“…This stretch was found in biochar and feedstock. However, the literature suggests that the gasification process can undo the aliphatic structure of the biomass [62,[64][65][66].…”
Section: Codmentioning
confidence: 99%
“…Biochar has significant potential in the remediation of pollutants from wastewater due to its unique physicochemical properties, including enriched surface functional groups (such as C − O, C O, COOH, and OH), a high specific surface area, pore structures, and cationic exchange capacity, all of which are beneficial for carbon sequestration ( Atukunda, Ibrahim, Fujii, Ookawara, & Nasr, 2022 ). Biochars remove contaminants from wastewaters through various mechanisms such as precipitation, surface complexation, ion exchange, pore filling, and electrostatic interactions.…”
Section: Applications Of Pea Pods As Valuable Waste Productsmentioning
confidence: 99%
“…9−11 Most of the conducted studies on TWS were on anaerobic digestion alone and/or in combination with other organic substrates, i.e., biogas production and nutrient-rich fertilizers for agriculture. 12,13 However, persistent heavy metals, dyes, and other chemical compounds in TWS are major constraints for its biological treatments, i.e., digestion, composting, and other thermal treatments, i.e., pyrolysis and incineration. 14−17 The direct combustion performance of TWS is weak due to the high content of inorganic materials, and for a similar reason, its heat content is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Realizing the rich nutrient and carbon content in TWS, many researchers have investigated various methods, namely, anaerobic digestion, incineration, composting, pyrolysis, cocombustion, advanced oxidation, and blending with concrete. The mentioned methods/treatments were explored to produce renewable biogas, char, compost manure, bricks, fuel materials, and mineralization of their organic components. Most of the conducted studies on TWS were on anaerobic digestion alone and/or in combination with other organic substrates, i.e., biogas production and nutrient-rich fertilizers for agriculture. , However, persistent heavy metals, dyes, and other chemical compounds in TWS are major constraints for its biological treatments, i.e., digestion, composting, and other thermal treatments, i.e., pyrolysis and incineration. The direct combustion performance of TWS is weak due to the high content of inorganic materials, and for a similar reason, its heat content is poor. Moreover, studies on combustion/cocombustion performance and dynamics revealed the release of volatile organics in the medium temperature range of 200–300 °C and then unsustained combustion at higher temperature ranges due to significant inert/inorganic content. , Moreover, the cocombustion of TWS is an area that needs to be further explored, as TWS has a low heat calorific value and high volatile content, which could be optimized by compositing with other organic substrates (potential waste materials) to reduce the problems related to the low combustion efficiency of TWS and also help in solid waste reduction, detoxification, and energy recovery.…”
Section: Introductionmentioning
confidence: 99%